Unveiling the Phytochemical Diversity and Bioactivity of Astragalus melanophrurius: A First Report Integrating Experimental and In Silico Approaches - Gulcan Gencer; Cengiz Sarikurkcu; Bektas Tepe (Pharmaceuticals)
Background: The genus Astragalus is renowned for its diverse bioactive potential, yet the chemical composition and biological properties of Astragalus melanophrurius remain inadequately explored. This study aimed to investigate the chemical profile, antioxidant capacity, and enzyme inhibitory activities of methanol extracts from various plant parts of A. melanophrurius. Methods: Methanol extracts were obtained from leaves, stems, flowers, roots, and aerial portions of A. melanophrurius. The chemical composition was determined using LC–ESI–MS/MS, focusing on key phytochemicals such as hyperoside, kaempferol, 4-hydroxybenzoic acid, and chlorogenic acid. Antioxidant activities were assessed via DPPH, ABTS, and FRAP assays, while enzyme inhibitory activities were evaluated against α-amylase and tyrosinase. In silico molecular docking analyses were conducted to explore the interactions between major compounds and target enzymes. Results: The leaf extract exhibited the highest total phenolic and flavonoid contents, correlating with superior antioxidant activities, achieving IC50 values of 16.55 mg/mL, 4.58 mg/mL, and 3.07 mg/mL in DPPH, ABTS, and FRAP assays, respectively. The root extract demonstrated notable α-amylase (IC50 = 2.99 mg/mL) and tyrosinase (IC50 = 1.34 mg/mL) inhibitory activities, suggesting potential applications in diabetes and hyperpigmentation management. Molecular docking revealed stable complexes of hyperoside and kaempferol with target enzymes, supporting their roles in observed bioactivities. Conclusions: This study highlights the bioactivity of A. melanophrurius extracts, particularly from leaves and roots, supporting their therapeutic potential. Future research should focus on isolating active compounds and conducting in vivo studies to confirm efficacy and elucidate mechanisms of action.